Techno-Economic Viability of Fuel Cell Emulator Toward Sustainable Energy Systems: A Survey - M. S. Priya; S. Saravanan; K. R. M. Vijaya Chandrakala; Umashankar Subramaniam; Sivakumar Selvam (IEEE Access)
This paper reviews the enhancement and implementation of a Fuel Cell (FC) emulator design to mimic the performance characteristics of a real FC. Unlike conventional methods, which require expensive and complex FC systems, the emulators are worthwhile solutions for steering cost-effective and harmless development. The system has fascinated the attention of worldwide producers and research groups in the field of grid, microgrid and electric vehicle applications. Emulators have made it possible to develop and optimise the system in both steady-state and transient behaviour, as well as power electronics and control, without the cost or harm of a physical FC system, making it a valuable device for researchers and engineers in the design and optimisation of the FC technologies. These systems enable the expansion and optimisation of FC-based power electronics, control strategies, and hybrid configurations without relying on or risking damage to actual FC stacks. Despite their critical role in accelerating research, comprehensive studies on FC emulators remain limited. This review provides an in-depth analysis of the working principles of fuel cells, emphasising the importance of FC stacks and the configuration of multi-stack fuel cells (MSFC). It explores fuel cell (FC) emulator evolution, categorizing them into pseudo, mathematical modelling, and electronic types, ensuring reliable performance comparable to real FC systems and assessing accuracy through the margin of error. The paper discusses control strategies, designing fuel cell emulators, and implementation techniques, addressing FC degradation issues and covering fault detection while suggesting solutions. It highlights current challenges in the reliability, durability, and scalability of fuel cells, supported by statistical analysis and techno-economic evaluations that demonstrate the benefits of emulator-based approaches. A case study illustrates hydrogen fuel cells’ role in sustainable development goals (SDGs), with a review of government policies contextualizing the push for clean energy technologies. This review provides researchers and engineers with essential tools to create advanced FC emulators, fostering innovation and overcoming barriers to FC adoption.